Analisis Spasial Tingkat Kepuasan Masyarakat dalam Pengelolaan Sampah di Kota Palembang - Masruroh, Ina; Wijayanti, Zetia; Pamungkas, Pandu (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Waste management is a critical public service that influences environmental quality and community welfare. Differences in urban spatial characteristics may affect the quality of waste management services and public satisfaction. This study aims to analyze differences in public satisfaction toward waste management across regional typologies in Palembang City. A quantitative comparative approach was employed using survey data collected from residents in six sub-districts representing city core, suburban, and fringe areas. Data were analyzed using descriptive statistics and the Kruskal–Wallis test due to non-normal data distribution. The results showed that the city core area had the highest average satisfaction score (M = 3.67), followed by suburban (M = 3.59) and fringe areas (M = 3.41). However, the Kruskal–Wallis test indicated that the differences were not statistically significant (H = 3.680; p = 0.159). Although no significant differences were found, a spatial pattern suggests lower satisfaction levels in areas farther from the city center. These findings emphasize the need to incorporate spatial considerations into waste management policies to achieve more equitable and effective service delivery.